'They're born to get breastfed'- how fathers view breastfeeding: a mixed method study - Emily Hansen; Leigh Tesch; Jennifer Ayton (BMC, 2018)
Abstract Background Fathers' attitudes and actions can positively or negatively affect mothers' intentions to breastfeed, breastfeeding duration and exclusivity. In-depth information about fathers' perspectives on breastfeeding are largely absent in the literature about infant feeding. The objective of this research was to investigate how fathers view breastfeeding. Methods This mixed method study recruited Tasmanian fathers with children < 24 months of age. Fathers completed a questionnaire and participated in either semi structured one-on-one or group interviews. Transcripts were analysed using a process of iterative thematic analysis. Results Twenty-six fathers participated in the study. They had a mean age of 34 years and just over half were first time fathers. A total of 13 fathers lived in areas classified by SEIFA as disadvantaged. Twenty-one reported they had decided as a couple to breastfeed their current child. Fathers' views on breastfeeding are complex, multi-layered and change over time: as babies get older, as fathers get more familiar with feeding babies, when feeding practices change and when family circumstances change. Four thematic categories related to how fathers view breastfeeding were identified; Breastfeeding as healthy and natural, the value of breast feeding and breastmilk, a pragmatic approach to breastfeeding and Breastfeeding as something achieved or imposed. Conclusion Fathers in our study valued breastfeeding and saw it as healthy and natural for babies. However, many of the fathers in our study had seen their partners struggle with breastfeeding. As a result some also viewed breastfeeding as a potentially harmful practice for mothers. Their accounts demonstrated that breastfeeding problems affect families, not just mothers and infants. There is scope for improvement in the care of women during and after birth to reduce breastfeeding problems and for fathers to learn more about breastfeeding prior to the birth of their child.